2017
DOI: 10.1007/s12011-017-1225-6
|View full text |Cite
|
Sign up to set email alerts
|

Hair Mineral and Trace Element Contents as Reliable Markers of Nutritional Status Compared to Serum Levels of These Elements in Children Newly Diagnosed with Inflammatory Bowel Disease

Abstract: Patients with inflammatory bowel disease (IBD) are at high risk for nutritional deficiencies because of long-term inflammation in the gut mucosa and decreased oral intake. Because inflammation responses affect serum micronutrient concentrations, serum levels are limited in reflecting body nutrient status in acute and chronic illness. We investigated the usefulness of measuring trace elements in hair as reliable markers of nutritional status compared to serum levels in children with IBD. We retrospectively anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 44 publications
4
40
1
Order By: Relevance
“…For example, Górski et al (2018) found that increase oral intake of Se caused a significant increase (p ≤ 0.05) in the Se concentration in the hair of animals. In turn, Cho and Yang (2018), based on their observation, suggested that hair better reflects Se status in organism than serum and therefore they recommend use of hair, as one of matrixes, to full analysis of selenium status. In addition, significant correlations between Se and Hg in hair was reported (Soares de Campos et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Górski et al (2018) found that increase oral intake of Se caused a significant increase (p ≤ 0.05) in the Se concentration in the hair of animals. In turn, Cho and Yang (2018), based on their observation, suggested that hair better reflects Se status in organism than serum and therefore they recommend use of hair, as one of matrixes, to full analysis of selenium status. In addition, significant correlations between Se and Hg in hair was reported (Soares de Campos et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Among the consequences of dietary changes, restrictive diets, and absorption deficiencies, malnutrition, whether it only includes protein malnutrition or micronutrient deficiencies as well, is a frequent diagnosis that can persist further on, as a consequence of altered intake, use of various drugs, or hypercatabolic state in this patient category [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most micronutrient status evaluations were performed by assessing serum levels [ 13 , 14 ], although the presence of chronic inflammation determines a high variability among these, independently of tissue stores [ 15 , 16 ]. Consequently, serum levels do not offer an accurate measure of trace element stores and trace element levels in hair have been proposed as a more reliable measurement of the chronic microelement nutritional status, considering that the systemic inflammatory response has been shown to independently decrease serum levels of micronutrients, including zinc, selenium, copper, and various vitamins, without any correlation to the actual nutritional status [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The morphological parameters of the blood were mostly normal, with the exception of low hemoglobin and hematocrit, and elevated monocyte counts in girls. Studies by Cho and Yang also indicate reduced parameters of hemoglobin and hematocrit in newly diagnosed patients [38]. Elevated monocytes were also observed in the study by Szczuko et al [39].…”
Section: Discussionmentioning
confidence: 62%